2010
DOI: 10.1158/1078-0432.ccr-09-3403
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Cellular Distribution, and Prognostic Relevance of TRAIL Receptors in Hepatocellular Carcinoma

Abstract: Purpose: After the advent of targeted therapies for hepatocellular carcinoma (HCC), much work is being done to provide a comprehensive description of the different signaling pathways contributing to cell survival and proliferation in this tumor. Apoptotic signaling mediated by tumor necrosis factorrelated apoptosis-inducing ligand (TRAIL) represents an important mechanism of tumor surveillance, but its importance in the development of HCC is not known. We thus investigated the cellular distribution and the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 33 publications
3
44
0
Order By: Relevance
“…Our report is consistent with the proposed role of the TRAIL-system in carcinogenesis [3-5], with previous observations from different tumour entities [6-8], with the recent report on pre-therapeutic baseline levels of OPG in rectal carcinoma patients [12], and with data from a large prospective epidemiological Norwegian study showing that OPG in serum correlates with cancer-related mortality [14]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our report is consistent with the proposed role of the TRAIL-system in carcinogenesis [3-5], with previous observations from different tumour entities [6-8], with the recent report on pre-therapeutic baseline levels of OPG in rectal carcinoma patients [12], and with data from a large prospective epidemiological Norwegian study showing that OPG in serum correlates with cancer-related mortality [14]. …”
Section: Discussionsupporting
confidence: 92%
“…In vivo investigation has shown that the TRAIL-system plays a role in the clearance of metastatic cells [2] and clinical data from human specimens have consistently shown a correlation between TRAIL-Receptor (TRAIL-R) loss and patients’ survival across different tumour entities [3-5]. Besides the downregulation of TRAIL-R1 and TRAIL-R2, apoptosis resistance can be caused by overexpression of decoy receptors for TRAIL (such as the membrane receptors TRAIL-R3 and TRAIL-R4 which competitively bind to TRAIL without inducing apoptotic signalling [1]) or by osteoprotegerin (OPG), a third, soluble form of the decoy receptor for TRAIL initially identified as a regulator of bone tissue modelling [1].…”
Section: Introductionmentioning
confidence: 99%
“…Other groups also reported a M30 increase [15] and TRAIL upregulation [7] in HCC. TRAIL signaling in HCC is of particular interest and a loss of TRAIL receptors has recently been described to further decrease the survival of HCC patients [16]. In contrast, Jing et al [17] reported FasR to be downregulated in some HCC tumors emphasizing the heterogeneity of this cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of antiapoptotic molecules like Bcl-2, Bcl-xL, IAPs or survivin are therefore commonly detected in human cancer and linked to poor prognosis [79,80,81,82,83,84,85,86]. Consequently, also the loss of proapoptotic factors like death receptors, adapter molecules or caspases has been observed in this context [87,88,89,90,91,92,93]. Interestingly, also the commonly observed increased expression or activity of growth-factor signaling cascades (e.g.…”
Section: Cell Death Deficiency In Cancermentioning
confidence: 99%